2020
DOI: 10.1590/0047-2085000000267
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of generalized anxiety disorder among elderly people in primary health care

Abstract: Objective To examine the prevalence of generalized anxiety disorder (GAD) and its associations with sociodemographic and health factors. Methods A cross-sectional study with a population-based sample of 578 individuals aged 60 years or older from the Family Health Strategy (FHS) program of Porto Alegre, RS, Brazil. Home visit screening and general data collection were made by trained Community Health Workers (CHWs). Diagnoses of psychiatric disorders were made by board-certified psychiatrists using the Mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
5
0
4
Order By: Relevance
“…Consistent with other studies, physical illness is a common risk factor for mental illness, particularly in the elderly. [20] In this context, we need to emphasize the importance of screening for anxiety and depression in PHC settings, especially when NCDs are present. , In our sample 41.1% suffer from depression, 39.2% from anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other studies, physical illness is a common risk factor for mental illness, particularly in the elderly. [20] In this context, we need to emphasize the importance of screening for anxiety and depression in PHC settings, especially when NCDs are present. , In our sample 41.1% suffer from depression, 39.2% from anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…al. 29 in Porto Alegre (RS), with a prevalence of 9% from the use of the Mini International Neuropsychiatric Interview plus (MINIplus). When combined, depression and anxiety symptoms are directly related to psychic suffering 15,23,27 which were assessed using the PHQ-4 instrument in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, the World Health Organization (WHO) estimated that the anxiety disorders affected 3.8% of the older population [2]. However, some studies had determinate prevalence between 9% and 11.4% in this population [4][5][6]. Furthermore, it has been shown that the frequency of anxiety is higher than the frequency of depression and cognitive disorders [7,8].…”
Section: Introductionmentioning
confidence: 99%